Potential of Stem Cells and CART as a Potential Polytherapy for Small Cell Lung Cancer - Skurikhin, Evgenii; Pershina, Olga; Zhukova, Mariia; Widera, Darius; Ermakova, Natalia; Pan, Edgar; Pakhomova, Angelina; Morozov, Sergey; Kubatiev, Aslan; Dygai, Alexander (Frontiers in Cell and Developmental Biology, 2021)
Despite the increasing urgency of the problem of treating small cell lung cancer (SCLC), information on the causes of its development is fragmentary. There is no complete understanding of the features of antitumor immunity and the role of the microenvironment in the development of SCLC resistance. This impedes the development of new methods for the diagnosis and treatment of SCLC. Lung cancer and chronic obstructive pulmonary disease (COPD) have common pathogenetic factors. COPD is a risk factor for lung cancer including SCLC. Therefore, the search for effective approaches to prevention, diagnosis, and treatment of SCLC in patients with COPD is an urgent task. This review provides information on the etiology and pathogenesis of SCLC, analyses the effectiveness of current treatment options, and critically evaluates the potential of chimeric antigen receptor T cells therapy (CART therapy) in SCLC. Moreover, we discuss potential links between lung cancer and COPD and the role of endothelium in the development of COPD. Finally, we propose a new approach for increasing the efficacy of CART therapy in SCLC.